RpoZ regulates 2,4-DAPG production and quorum sensing system in Pseudomonas fluorescens 2P24 - Wei, Yarui; Dong, Baozhu; Wu, Xiaogang; Zhao, Mingmin; Wang, Dong; Li, Na; Zhang, Qian; Zhang, Liqun; Zhou, Hongyou (Frontiers in Microbiology, 2023)
Introduction: Pseudomonas fluorescens (P. fluorescens 2P24) was isolated from soil of natural decay associated with wheat take-all and it can effectively control soil-borne diseases caused by a variety of plant pathogens. 2,4-diacetylphloroglucinol (2,4-DAPG), is produced by P. fluorescens 2P24 and plays an important role in the prevention and control of plant diseases. To understand the resistant mechanism, in this study, we conducted experiments to explore the regulation role of rpoZ in the synthesis of the antibiotic 2,4-DAPG and regulation of QS system. Methods: A random mini-Tn5 mutagenesis procedure was used to was used to screen regulators for phlA transcriptional in reporter stain PM901, which containing a chromosomal phlA∷lacZ transcriptional fusion,. We identified 12 insertion mutants could significantly change phlA gene expression. By analyzing the amino acid sequences of the interrupted gene, we obtained a mutant strain Aa4-29 destroyed the rpoZ gene, which encodes the omiga subunit. We constructed the plasmids of ropZ mutant (pBBR-△rpoZ) transformed into competent cells of P.fluorescens 2P24 by electro-transformation assay. The strains of P. fluorescens 2P24/pBBR、2P24-△rpoZ/pBBR、2P24-△rpoZ/pBBR-rpoZ were used to evaluate the regulation role of rpoZ in 2,4-DAPG production and quorum sensing system. Results: According to β-galactosidase activity, we found that rpoZ positively regulated the expression of phlA (a synthesis gene of 2,4-DAPG) and PcoI (a synthesis gene of PcoI/PcoR QS system signal) at the transcriptional level. The production of 2, 4-DAPG antibiotic and signal molecule AHL was influenced by rpoZ. Further, rpoZ is involved in regulating rsmA expression, which affecting 2,4-DAPG production. rpoZ also has a certain regulatory effect on rpoS transcription, but not on the transcription of phlF, emhABC and emhR. According to the biocontrol assay, strains with ropZ showed obvious antagonism ability against the Rhizocaritis ristilis in cotton, while the mutant strain of rpoZ lost the biocontrol effect. rpoZ had a significant effect on the swimming and biofilm formation in P. fluorescens 2P24. Conclusion: Our data showed that rpoZ was an important regulator of QS system, 2,4-DAPG in P. fluorescens 2P24. This may imply that P. fluorescens 2P24 has evolved different regulatory features to adapt to different environmental threats.